2008
DOI: 10.1007/s12072-008-9067-0
|View full text |Cite
|
Sign up to set email alerts
|

New concepts in the immunopathogenesis of chronic hepatitis B: the importance of the innate immune response

Abstract: Acute and chronic infection with hepatitis B virus (HBV) is associated with an increased risk of developing liver disease including cirrhosis, decompensated liver disease, and hepatocellular carcinoma. The clinical presentation and natural history of HBV infection is mediated through complex interactions between the virus and the host immune response. HBV is not directly cytopathic to heptocytes; however, the interaction between the virus and the host immune response plays a central role in the pathogenesis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 66 publications
0
19
0
1
Order By: Relevance
“…Although innate immune responses appear mainly to be downregulated in chronic hepatitis B,18 innate immune mechanisms have already been shown to play an important role in pathogenesis of liver damage in chronic hepatitis B, particularly during hepatitis B flares,19 20 and in chronic hepatitis B necroinflammatory activity and liver cirrhosis 21. The mechanisms for these are still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Although innate immune responses appear mainly to be downregulated in chronic hepatitis B,18 innate immune mechanisms have already been shown to play an important role in pathogenesis of liver damage in chronic hepatitis B, particularly during hepatitis B flares,19 20 and in chronic hepatitis B necroinflammatory activity and liver cirrhosis 21. The mechanisms for these are still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Whether HBV infection is cleared or persists as a progressive liver disease is determined by both viral and host factors. 1,2 It has been demonstrated that activation of pathogen recognition receptors (PRRs), including TLRs, RIG-I, and melanoma differentiationassociated gene 5 (MDA-5), can induce the inhibition of HBV replication via innate immune responses. 20 The local innate immune responses of the liver play major roles in inhibiting HBV replication, especially through the production of large amounts of antiviral cytokines (particularly type I IFN).…”
Section: Discussionmentioning
confidence: 99%
“…Whether HBV infection is cleared or persists as a progressive liver disease is determined by interaction between virus and host factors. 1,2 Although type I interferons (IFNs) can suppress HBV replication, the virus has the counteracting mechanisms to suppress the production and function of IFNs, leading to immune tolerance. For instance, HBV suppresses MxA expression at the promoter level or by inhibiting cellular proteasome activities in an HBV X gene (HBx)-dependent manner.…”
Section: Hronic Hepatitis B Virus (Hbv) Infection Ismentioning
confidence: 99%
“…HBeAg seroconversion is typically preceded by hepatic flares characterized by increases in ALT levels, which signify an enhanced endogenous cellular T lymphocyte-mediated response against HBV [21]. Identifying the precise mechanisms involved in triggering immune response leading to HBeAg seroconversion is a focus of ongoing research [22,23].…”
Section: Hbeag Seroconversion and Disease Outcomes In Patients With Chbmentioning
confidence: 99%